Gender and age features of clinical and psychopathological phenomenology of depressive disorders in modern times - О. O. Belov; N. H. Pshuk (Zaporožskij Medicinskij Žurnal)
The aim of the work was to study the gender and age features of the clinical and psychopathological phenomenology of depressive disorders at the present stage.